Lumbar spinal stenosis: the reliability, sensitivity and specificity of the nerve root sedimentation sign - Azizan, Asrul Fahmi (2015)

(untitled)
Introduction: Lumbar spinal stenosis (LSS) is a medical condition in which the spinal canal narrows and compresses the spinal cord and nerves at the level of the lumbar vertebra. The sedimentation sign is evaluated from standard lumbar MRIs and easy to apply. MRI finding of positive sedimentation sign is a reliable sign to diagnose lumbar spinal stenosis with high sensitivity and specificity. The objective of this study is to identify the nerve root sedimentation sign in patients with degenerative LSS and to evaluate its reliability, sensitivity and specificity. Methodology: This study is a retrospetive record review study to determine the socio-demographic and clinical presentation of LSS. It is also to determine the reliability, sensitivity and specificity of the nerve root sedimentation sign and to evaluate the inter and intra observer reliability, sensitivity and specificity. 82 subjects were enrolled in this study to determine the socio-demographic, clinical presentation of LSS, reliability, sensitivity and specificity of the nerve root sedimentation sign. 56 subjects were included in determining the inter and intra observer reliability, sensitivity and specificity. Two observers which were a radiologist and an orthopaedic surgeon were assigned to independently elicit the sign. Results: There were 43 patients in LSS group and 39 patients for control (non LSS group). There was significant association between spinal claudication and leg numbness with LSS (p <0.001). Leg weakness, buttock pain and thigh pain also showed significant association with LSS (p = 0.037, 0.019 and 0.011 respectively). There were significant association ofmotor weakness and sensory changes with LSS (p <0.001). The nerve root sedimentation sign were 100% sensitive in diagnosed LSS with specificity of 82.1%. The sensitivity of the nerve root sedimentation by Observer 1 was 84.8% and Observer 2 was 78.8% while the specificity by both observers was 95.7%. For the intra observer reliability, both observers showed good reliability. The intra observer reliability for Observer 1 was Kappa of 0.785, (p value < 0.001) 95% CI (0.62, 0.95) and the intra observer reliability for Observer 2 was Kappa of 0.857, (p value < 0.001) 95% CI (0.72, 0.99). The inter observer reliability for two observers was found to be good with Kappa of 0.610, (p value < 0.001) 95% CI (0.62, 0.95). Conclusion: The results showed that the nerve root sedimentation sign had high sensitivity and specificity for diagnosing LSS. For the intra rater reliability, both observers showed good reliability. This showed that this sign can be identified accurately and it gives reliable additional information in diagnosing LSS.